2022
DOI: 10.33225/jbse/22.21.720
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge Integration in Student Learning of Buoyant Force

Abstract: Students’ problem-solving ability depends on their understanding of related scientific concepts. Therefore, the modeling and assessment of students’ understanding of specific scientific concepts is important to promote students’ problem-solving ability, as it can find students’ understanding difficulties and explore breakthrough strategies accordingly. Inspired by the theory of knowledge integration and combined with the situational characteristics of science education in China, this study established a conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…The results of data analysis showed that understanding the nature has a significant effect on students' forming an integrated knowledge structure of buoyancy. Although this conclusion is consistent with previous relevant research studies, this study has made new progress in presenting students' cognitive schematics and teaching method design of helping students understand the nature of buoyancy (Gao et al, 2020;Paik et al, 2017;Zou et al, 2022). Therefore, more teaching methods that can help students understand the nature of buoyancy, as well as more logical conceptual frameworks about buoyancy, should be sought to help students better understand the nature of buoyancy and develop a more comprehensive knowledge integration of buoyancy.…”
Section: The Teaching Of Emphasizing the Nature Of Buoyancy Is Effect...supporting
confidence: 84%
See 1 more Smart Citation
“…The results of data analysis showed that understanding the nature has a significant effect on students' forming an integrated knowledge structure of buoyancy. Although this conclusion is consistent with previous relevant research studies, this study has made new progress in presenting students' cognitive schematics and teaching method design of helping students understand the nature of buoyancy (Gao et al, 2020;Paik et al, 2017;Zou et al, 2022). Therefore, more teaching methods that can help students understand the nature of buoyancy, as well as more logical conceptual frameworks about buoyancy, should be sought to help students better understand the nature of buoyancy and develop a more comprehensive knowledge integration of buoyancy.…”
Section: The Teaching Of Emphasizing the Nature Of Buoyancy Is Effect...supporting
confidence: 84%
“…The reliability of this test has been verified in another study (Zou et al, 2022). This study was used to analyze the effect of understanding the nature of buoyancy on corresponding knowledge integration after the teaching experiment.…”
Section: The Assessment Questionsmentioning
confidence: 87%